Arthroscopic Centralization for Lateral Meniscal Injuries Reduces Laxity in the Anterior Cruciate Ligament–Reconstructed Knee. Issue 13 (November 2021) - Nakamura, Tomomasa; Marshall, Brandon D.; Price, Taylor M.; Mao, Yongtao; Linde, Monica A.; Koga, Hideyuki; Smolinski, Patrick; Fu, Freddie H.
Background: A lateral meniscal (LM) disorder is one factor that causes rotational laxity after anterior cruciate ligament (ACL) reconstruction (ACLR). There are different types of irreparable meniscal disorders, one of which is a massive meniscal defect. Hypothesis/Purpose: The purpose of this study was to evaluate the kinematic effects of arthroscopic centralization on an irreparable LM defect. The hypothesis was that arthroscopic centralization for an irreparable LM defect with concomitant ACLR would improve knee rotational stability. Study Design: Controlled laboratory study. Methods: A total of 14 fresh-frozen human cadaveric knees were tested in 4 states: (1) intact ACL and intact lateral meniscus, (2) reconstructed ACL and intact lateral meniscus, (3) reconstructed ACL and lateral meniscus defect, and (4) reconstructed ACL and centralized lateral meniscus. Anatomic ACLR was performed using an 8 mm–diameter hamstring tendon graft. An LM defect (20% of the anteroposterior length) was created arthroscopically, and arthroscopic centralization was performed. Kinematics were analyzed using a 6 degrees of freedom robotic system under 4 knee loads: (1) an 89.0-N anterior tibial load, (2) a 5.0-N·m external rotation tibial torque, (3) a 5.0-N·m internal rotation tibial torque, and (4) a simulated pivot-shift load with a combined 7.0-N·m valgus and 5.0-N·m internal rotation tibial torque. Results: LM centralization reduced anterior tibial translation similar to that of the ACLR intact LM state under anterior tibial loading (~2 mm at 30° of flexion) and showed 40% to 100% of tibial displacement in the 4 knee states under simulated pivot-shift loading. The procedure overconstrained the knee under internal rotation tibial torque and simulated pivot-shift loading. Conclusion: Arthroscopic centralization reduced knee laxity after ACLR for a massive LM defect in a cadaveric model. Clinical Relevance: In cases involving irreparable LM injuries during ACLR, consideration should be given to arthroscopic centralization for reducing knee laxity. However, the procedure may overconstrain the knee in certain motions.